PENGARUH JOB DESCRIPTION DAN KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN KANTOR PUSAT CV CALYSTA PRIMA AESTHETIC - Priyana, Indarta; Ismail, Fajar; Retnowati, Ayu Nike (LPPM UNIBI, 2020)
This study aims to determine the description of the job description and compensation and job satisfaction as well as the magnitude of the effect, either partially or simultaneously on the employees of the CV Calysta Prima Aesthetic center. The method used in this research is descriptive method and verification method. The population in this study were employees of the CV Calysta Prima Aesthetic center, with a total sample of 39 people with saturated sampling technique. Based on the results of the study, it was found that the job description and compensation were in the good category, while job satisfaction was in the medium/high enough category. Based on the results of the study, it was obtained that the job description partially gave an effect of 81.2%. The effect of compensation partially gives an effect of 84.9% on employee job satisfaction. The effect of job description and compensation simultaneously gives an effect of 86.9% on employee job satisfaction.